Running Distance and Biomechanical Risk Factors for Plantar Fasciitis: A 1-yr Prospective 4HAIE Cohort Study - Plesek, Jan; Hamill, Joseph; Burda, Michal; Elavsky, Steriani; Skypala, Jiri; Urbaczka, Jan; Freedman-Silvernail, Julia; Zahradnik, David; Uchytil, Jaroslav; Jandacka, Daniel (Medicine and science in sports and exercise, 2025)
INTRODUCTION: Plantar fasciitis (PF) is one of the most common running-related injuries. PURPOSE: The aim of this prospective study was to determine the incidence of PF and identify potential risk or protective factors for PF in runners and non-runners. METHODS: Data from 1206 participants from the 4HAIE cohort study (563 females/643 males; 715 runners/491 non-runners; 18–65 yr of age) were included in the analysis. We collected biomechanical data during overground running using a three-dimensional motion capture system at the baseline and running distance data via retrospective questionnaires and followed the participants for 12 months following the baseline data collection. Participants were asked weekly about any sports-related injury (including PF). A binary logistic regression was performed to reveal potential associations between running distance and biomechanical risk factors and PF while controlling for running distance, sex, and age. RESULTS: The total incidence of PF was 2.3% (28 PF from 1206 participants), 2.5% in runners and 2.0% in non-runners (P = 0.248). Runners who ran more than 40 km·wk−1 had six times higher odds of suffering PF than individuals who ran 6–20 km·wk−1 (P = 0.009). There was a significant association between maximal ankle eversion and PF; that is, runners with a greater eversion angle during the stance period had higher risk of PF (P = 0.024). No other biomechanical variables indicated significant associations with PF. CONCLUSIONS: Regular running with a moderate weekly volume and more toeing out of the foot relative to the shank may reduce the risk against PF in runners, which may be useful for researchers, runners, coaches, and health professionals to minimize PF injury risk.
Keywords: Running; biomechanika; lidé; mladiství; Adult; Middle Aged; Risk Factors; prospektivní studie; Female; Fasciitis, Plantar; Incidence; Adolescent; Humans; Prospective Studies; lidé středního věku; mužské pohlaví; mladý dospělý; fasciitida plantární; Biomechanical Phenomena; ženské pohlaví; Young Adult; Male; Aged; incidence; běh; dospělí; rizikové faktory; senioři